Wedge resection versus segment IVb and V resection of the liver for T2 gallbladder cancer: a systematic review and meta-analysis - Chen, Zhehan; Yu, Jiayu; Cao, Jiasheng; Lin, Chenping; Hu, Jiahao; Zhang, Bin; Shen, Jiliang; Feng, Xu; Topatana, Win; Chen, Mingyu; Fang, Haixing (Frontiers in Oncology, 2023)
Objectives: Although guidelines recommend extended cholecystectomy for T2 gallbladder cancer (GBC), the optimal hepatectomy strategy remains controversial. The study aims to compare the prognosis of T2 GBC patients who underwent wedge resection (WR) versus segment IVb and V resection (SR) of the liver. Methods: A specific search of online databases was performed from May 2001 to February 2023. The postoperative efficacy outcomes were synthesized and meta-analyses were conducted. Results: A total of 9 studies involving 2,086 (SR = 627, WR = 1,459) patients were included in the study. The primary outcomes included disease-free survival (DFS) and overall survival (OS). For DFS, the 1-year DFS was statistically higher in patients undergoing SR than WR [risk ratio (RR) = 1.07, 95% confidence interval (CI) = 1.02-1.13, P = 0.007]. The 3-year DFS (P = 0.95), 5-year DFS (P = 0.77), and hazard ratio (HR) of DFS (P = 0.72) were similar between the two groups. However, the 3-year OS was significantly lower in patients who underwent SR than WR [RR = 0.90, 95% CI = 0.82-0.99, P = 0.03]. Moreover, SR had a higher hazard HR of OS [HR = 1.33, 95% CI = 1.01-1.75, P = 0.04]. No significant difference was found in 1-year (P = 0.32) and 5-year (P = 0.9) OS. For secondary outcomes, patients who received SR tended to develop postoperative complications (POC) [RR = 1.90, 95% CI = 1.00-3.60, P = 0.05]. In addition, no significant differences in intrahepatic recurrence (P = 0.12) were observed. Conclusions: In conclusion, SR can improve the prognosis of T2 GBC patients in DFS. In contrast to WR, the high HR and complications associated with SR cannot be neglected. Therefore, surgeons should evaluate the condition of the patients and take their surgical skills into account when selecting SR.